The syntactic preferences of Mohieddin Darwish in his book "Explanation and Explanation of the Qur'an" - Amiri, Jahangir; Al-Rawwas, Salah Mohsin Hazim; Al-Anbaki, Mohamed Zaher AbdelMohsin (Journal of Arabic Language Sciences and Literature, 2023)
The grammatical and linguistic efforts of Mohieddin Darwish in his book The Expression of the Qur’an and Its Explanation are among the most important grammatical and linguistic efforts in the modern era. In view of the efforts he made to serve the Book of God in order to get rid of the many differences in syntax and the like, and in view of his choices and judgments in giving preference to controversial issues. Where it tracks the most correct opinions, avoids abnormal and weak opinions, shows the differences in a clear and short phrase, and avoids saying the opinion and violating the previous ones, and one of the most important efforts made by the rectification on the part of the right in the far and wrong aspects of the expression, which includes the correct form with the correctness The controversy between the interpreters and the grammarians, and their opinions varied about it, represented by the sentences performing the function of nouns, which is outside the issue of grammatical measurements, as it is an issue that needed to be addressed due to the large number of places in which the sentences leading to the two questions in the Qur’an lead to the two functions of the research. Darwish was in most places of writing in agreement with his preferences for the opinions of the ancient Arabizers, and that he was mostly embarrassed by the response or criticism of a face, and he was interested in his book in the expression of the Conjugative texts word for word without going into the issue of the difference between them. That was ignorant of him, but because the purpose of the author of his book is an educational purpose, so he distanced himself from the issue of signification and elucidation.
Keywords: parsing; pronunciation; rectification; Mohieddin Darwish